A10.9 Evidence for Progressive Reduction and Loss of Telocytes in the Dermal Cellular Network of Systemic Sclerosis. (25th February 2013) - Manetti, Mirko; Guiducci, Serena; Ruffo, Martina; Rosa, Irene; Faussone-Pellegrini, Maria Simonetta; Ibba-Manneschi, Lidia; Matucci-Cerinic, Marco
Abstract : Background and Objectives: Telocytes are a distinct population of stromal cells which have been recently identified in a wide variety of tissues and organs, including the skin. By their extremely long cytoplasmic processes telocytes may act as supporting cells and form a scaffold to define the correct three-dimensional organisation of tissues/organs during pre-natal life, or their repair/renewal in post-natal life. Moreover, telocytes may influence the transcriptional activity of neighbouring stromal cells (fibroblasts/myofibroblasts, mast cells), either by cell-to-cell contacts or by secreting paracrine signalling molecules, and may be implicated in tissue regeneration by cooperating with stem cell niches to form tandem cell structures. Systemic sclerosis (SSc) is a complex connective tissue disease characterised by fibrosis of the skin and internal organs. Up to now, most of the studies have focused on fibroblasts/myofibroblasts, while little is known about the possible involvement of other stromal cell types in SSc pathophysiology. In the present study, we investigated the distribution and ultrastructural features of telocytes in the skin of SSc patients compared with normal skin. Methods: Forearm skin biopsies were obtained from 24 SSc patients (13 limited cutaneous SSc (lcSSc), 11 diffuse cutaneous SSc (dcSSc)) and 10 healthy controls. Skin sections were subjected to immunoenzymatic or immunofluorescence labelling for CD34, CD31/PECAM-1, alpha-smooth muscle actin (alpha-SMA), CD11c, CD90/Thy-1, c-kit/CD117 and mast cell tryptase. Ultrathin sections were processed for transmission electron microscopy (TEM). Results: By an integrated immunohistochemical and TEM approach, we confirmed that telocytes were present in human dermis, where they were mainly recognisable by their typical ultrastructural features and were immunophenotypically characterised by CD34 expression. Dermal telocytes were immunophenotypically negative for CD31/PECAM-1 (endothelial cells), alpha-SMA (myofibroblasts, pericytes/vascular smooth muscle cells), CD11c (dendritic cells/macrophages), CD90/Thy-1 (fibroblasts) and c-kit/CD117 (mast cells). In normal skin, telocytes were organised to form three-dimensional networks distributed among collagen bundles and elastic fibres, and surrounded microvessels, nerves and skin adnexa (hair follicles, sebaceous and sweat glands). Telocytes displayed severe ultrastructural damages (swollen mitochondria, cytoplasmic vacuolisation, lipofuscinic bodies) suggestive of ischaemia-induced cell degeneration and were progressively lost from the clinically affected skin of SSc patients. Telocyte damage and loss evolved differently according to lcSSc/dcSSc subsets and early/advanced stages, being more rapid and severe in dcSSc. Conclusions: In SSc skin, the progressive loss of telocytes might i) contribute to the altered three-dimensional organisation of the extracellular matrix, ii) reduce the control of fibroblast/myofibroblast and mast cell activity, and iii) impair skin regeneration and/or repair.